2009
DOI: 10.1080/09286580902999389
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Trachoma among Children Living in Rural Northern India

Abstract: Active trachoma is not a public health problem in previously hyperendemic areas of North India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…4 Results of a rapid assessment for active trachoma have been reported from an area near the national capital which was known to be previously hyperendemic and it was observed that the area was no longer hyperendemic. 5 However data on the burden of cicatricial trachoma is lacking. Data from previous studies confirm the perception that women have a greater burden of trichiasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Results of a rapid assessment for active trachoma have been reported from an area near the national capital which was known to be previously hyperendemic and it was observed that the area was no longer hyperendemic. 5 However data on the burden of cicatricial trachoma is lacking. Data from previous studies confirm the perception that women have a greater burden of trichiasis.…”
Section: Discussionmentioning
confidence: 99%
“…4 We have previously reported results of trachoma rapid assessment (TRA) for active trachoma in children living in hyperendemic areas in North India. 5 In the present study we performed a rapid assessment study in adult females in a previously hyperendemic area in North India.…”
mentioning
confidence: 99%
“…The success of various health programmes cannot be denied, but the trachoma persisted and now has shown upsurge, due to lack of awareness and interest by government agencies. Trachoma prevalence in India has been reported to be varying between 0.5 to 80 per cent, according to studies conducted across various centers [6][7][8][9][10][11][12][13]. Community studies were conducted to find out the true prevalence of Chlamydia trachomatis infection using laboratory support in the known hyperendemic belt of northern India by the Trachoma Study Group in 1998 (Uttar Pradesh) and later in 2007-2008 (Haryana) [5,9].. Sharma et al from RP Center, AIIMS did a twelve year study (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) in rural northern India and has shown the prevalence of trachoma to be persisting in northern India, albeit at a lower level [14].…”
Section: Discussionmentioning
confidence: 99%
“…[37] In a laboratory-based field study in hyperendemic areas of Uttar Pradesh (Bulandshahr and Dehradun districts), in 1998, the prevalence rate of 8.5% active trachoma among 837 children in the age-group of 1–10 years was reported. [38] In small studies in Delhi in 1999 and 2004 suggested, trachoma was common in Delhi school children[3940] In 2005, another laboratory-based study was conducted in rural areas of Mewat region of Haryana; in 1000 children (age: 1–9 years), the prevalence of active trachoma was 4% and in 1000 adult females (500 between 15 and 30 years and the rest over 30 years), the prevalences were of TS 26.4%, TT 5.4%, and trachomatous CO 3.2%. [3841]…”
Section: Epidemiologymentioning
confidence: 99%